Feedstock properties and debinding mechanism of yttria-stabilized zirconia/ stainless steel 17-4PH micro-components fabricated via two-component micro-powder injection molding process. Issue 14 (15th July 2021) - Basir, Al; Sulong, Abu Bakar; Jamadon, Nashrah Hani; Muhamad, Norhamidi
Abstract: Two-component micro-powder injection molding (2C-μPIM) is a promising technique to produce bi-material micro-sized components of 3 mol% yttria-stabilized zirconia (3YSZ) and 17-4PH stainless steel (SS 17-4PH). In this research, the solvent and thermal debinding mechanisms of the green 3YSZ/SS 17-4PH micro-parts were investigated using a systematic approach. For obtaining the feedstocks, 3YSZ and SS 17-4PH powders were individually mixed with palm stearin and low-density polyethylene (LDPE) binders. This experimental work revealed that the palm stearin elimination rate in 3YSZ/SS 17-4PH micro-parts consisted of 3YSZ and SS 17-4PH feedstocks with powder loadings of 44 vol% and 69 vol%, respectively, increased with an increase in the temperature during the solvent debinding process. While a substantial amount of palm stearin was removed from the interface and other regions of the bi-material micro-component at the solvent debinding temperature of 70 °C, the joining between 3YSZ and SS 17-4PH collapsed at 80 °C. The open channels that developed in the component solvent debound at 70 °C helped to eliminate 96%–99% of the binder system in the thermal debinding stage. After the sintering, the findings signified that bi-material micro-components could be fabricated successfully through the process route of 2C-μPIM by using the feedstocks of 3YSZ and SS 17-4PH.